Possibilities for Experimental Testing of Alarm Transmission Systems - Martin Boros; Matej Kucera; Andrej Velas; Jan Valouch (Communications - Scientific letters of the University of Zilina, 2020)
In the current digital era, information is a basis of some systems. In the area of information, great emphasis is also placed on its security and possibilities of use. The basis of the alarm transmission system is information about the protected object, which is transmitted to the remote center of the alarm transmission system. Operators of alarm transmission system centers should be obliged to carry out regular testing of the availability of individual transmission networks. At present, there is a trend that those tests are carried out by telephone calls between the two technicians and the time of transmission of information is measured utilizing a stopwatch. To automate this process, a test facility has been created that can simulate and record the intrusion of a protected object. Initial experimental tests have ascertained whether it is possible, with the test equipment, to generate the data necessary to assess the reliability of alarm transmission systems.